Stability Analysis Of Construction Design Reservoir Slopes Based On Numerical Simulation At Ulu Jelai Hydroelectric Dam Project, Cameron Highland, Pahang, Malaysia - Md. Yusof, Nur Qurrahtin A’ini (2019)
A slope stability study alongside the right bank rim of Susu Dam reservoir was conducted to analyse the stability of the reservoir slopes. The factors of safety (FOS) under the loadings of steady-state seepage and transient seepage condition were determined by using Finite Element Method-Shear Strength Reduction (FEM SSR). A total of fourteen slopes have been analysed in this study. Only a slope A1-A2 is analysed under transient seepage since it is a critical slope which is near to dam. The analysis of stability was conducted based on desk study, geological condition and geotechnical properties. A RS2 9.0 program was used to conduct the analysis of reservoir slope under various loading based on geotechnical data obtained. Based on the FOS of steady-state seepage analysis of the slopes under normal condition, it can be concluded that slopes are safe and stable since most of the determined FOS are beyond minimum FOS 1.5. However, the FOS of some of the slope under flood condition is below minimum FOS of 1.5. Meanwhile, the FOS of the slopes under drawdown condition was beyond minimum FOS of 1.2. Thus, the slopes are also considered stable. Based on transient seepage analysis, the slope was analysed under different hydraulic conductivity of the soil slope with different drawdown rates. Slope A1-A2 was failed under drawdown rates of 2 m/d with hydraulic conductivity of 1x10-6 m/s since the rate of decreases in the reservoir water level is greater than hydraulic conductivity. Therefore, sensitivity of the water level to the stability of the slope should be given more attention and prediction of worst groundwater condition is necessary. A regular maintenance of subsurface drainage system is required to prevent reduction of efficiency caused by siltation, deterioration of seals or growth of vegetation blocking the outlet.